Law No. 10 of the year 2019 Amending Certain Provisions of the Income Tax Law No. 91 of the Year 2005 = قانون رقم 10 لسنة 2019 بتعديل بعض أحكام قانون الضريبة على الدخل الصادر بالقانون رقم 91 لسنة 2005 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic